1998
DOI: 10.1172/jci1130
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-induced apoptosis in rat dorsal root ganglion neurons is associated with attempted entry into the cell cycle.

Abstract: Platinum compounds induce apoptosis in malignant cells and are used extensively in the treatment of cancer. Total dose is limited by development of a sensory neuropathy. We now demonstrate that when rats are administered cisplatin (2 mg/kg i.p. for 5 d), primary sensory neurons in the dorsal root ganglion die by apoptosis. This was reproduced by exposure of dorsal root ganglion neurons and PC12 cells to cisplatin (3 microg/ml) in vitro. Apoptosis was confirmed by electron microscopy, DNA laddering, and inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
138
0
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(147 citation statements)
references
References 71 publications
5
138
0
4
Order By: Relevance
“…Our present data suggest that one pathway may be through the phosphorylation of pRb. Consistent with this, it has been reported that pRb phosphorylation has been observed in in vitro cultured neurons exposed to apoptotic stress (12,19,36) and that overexpression of pRb is protective in models of embryonic cortical death evoked by DNA damage (13). In addition, there is increased developmental neuronal death in pRb-deficient mice (37,38).…”
Section: Discussionsupporting
confidence: 65%
“…Our present data suggest that one pathway may be through the phosphorylation of pRb. Consistent with this, it has been reported that pRb phosphorylation has been observed in in vitro cultured neurons exposed to apoptotic stress (12,19,36) and that overexpression of pRb is protective in models of embryonic cortical death evoked by DNA damage (13). In addition, there is increased developmental neuronal death in pRb-deficient mice (37,38).…”
Section: Discussionsupporting
confidence: 65%
“…18 Since then, neuronal levels of cyclin D1 transcripts and/or protein have been reported to be elevated in response to a wide range of apoptotic stimuli in vitro, in vivo and in neurodegenerative diseases. For culture systems, this includes cerebellar granule neurons switched from culture medium containing depolarizing levels of K þ to one containing low levels of K þ 26-29 (we shall henceforth refer to this model as 'repolarization'), cerebellar granule neurons exposed to kainic acid, 30 cortical neurons exposed to beta amyloid protein, 31 sensory neurons exposed to cisplatin 32 and serum-deprived neuroblastoma cells. 33 In the repolarization model, the distribution of cyclin D1 also appeared to change from a diffuse cytoplasmic pattern to a nuclear localization.…”
Section: Cyclin D1mentioning
confidence: 99%
“…Stimuli including camptothecin, 92 cisplatin, 32 beta amyloid, 31 repolarization 27,68 and proteasome inhibitors 73 promote pRb phosphorylation in cultured neurons. Similar findings pertain to p107.…”
Section: Rb/pocket Proteins and Neuron Deathmentioning
confidence: 99%
“…[7,28]. In addition, MAPK kinase pathways including Cisplatin has been reported to induce apoptosis in neuronal extracellular signal-regulated kinase (ERK), c-JUN aminocells [1,5,10,12,18,20]. However, its precise signaling terminal protein kinase (JNK) and p38 MAPK were mechanism involved in cisplatin-induced apoptosis is not reported to be involved in signaling pathway induced by fully understood.…”
Section: Introductionmentioning
confidence: 99%